Moments of zeta and correlations of divisor-sums: V - Conrey, B; Keating, J (London Mathematical Society, 2018)
In this series of papers we examine the calculation of the 2kth moment and shifted moments of the Riemann zeta-function on the critical line using long Dirichlet polynomials and divisor correlations. The present paper completes the general study of what we call Type II sums which utilize a circle method framework and a convolution of shifted convolution sums to obtain all of the lower order terms in the asymptotic formula for the mean square along [T, 2T] of a Dirichlet polynomial of arbitrary length with divisor functions as coefficients.